Postglacial expansion pathways of red mangrove, Rhizophora mangle, in the Caribbean Basin and Florida. Issue 2 (2nd February 2016) - Kennedy, John Paul; Pil, Maria W.; Proffitt, C. Edward; Boeger, Walter A.; Stanford, Alice M.; Devlin, Donna J.
Abstract : PREMISE OF THE STUDY: The Last Glacial Maximum (LGM) was a period of massive range contraction. Post‐LGM, water‐dispersed coastal species, including the red mangrove ( Rhizophora mangle ), expanded poleward as propagules were transported by ocean currents. We assessed postglacial marine expansion pathways for R. mangle within the Caribbean Basin and Florida. METHODS: Six microsatellite loci were used to genotype 237 individuals from nine R. mangle populations in the Caribbean, Florida, and Northwest Africa. We evaluated genetic variation, population structure, gene flow along alternative post‐LGM expansion pathways to Florida, and potential long‐distance dispersal (LDD) from West Africa to Caribbean islands. KEY RESULTS: These R. mangle populations had substantial genetic structure ( F ST = 0.37, P < 0.0001) with three discrete population clusters (Caribbean mainland, Caribbean islands, and Florida). Genetic connectivity along the mainland pathway (Caribbean mainland to Florida) vs. limited gene dispersal along the Antilles Island pathway (Caribbean islands to Florida) supported Florida recolonization from Caribbean mainland sources. Genetic similarity of Northwest Africa and two Caribbean islands provided evidence for trans‐Atlantic LDD. We did not find a pattern of decreasing genetic diversity with latitude. CONCLUSIONS: We outline a complex expansion history for R. mangle, with discrete pathways of recolonization for Florida and Caribbean islands. Contrary to expectation, connectivity to putative Caribbean mainland refugial populations via ocean currents, and not latitude, appears to dictate genetic diversity within Caribbean island and Florida R. mangle . These findings provide a framework for further investigation of additional water‐dispersed neotropical species, and insights for management initiatives.